2002
DOI: 10.1098/rspb.2001.1931
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress, inbreeding, and the nature of phenotypic and genetic variance inDrosophila melanogaster

Abstract: Fifty-two lines of Drosophila melanogaster founded by single-pair population bottlenecks were used to study the effects of inbreeding and environmental stress on phenotypic variance, genetic variance and survivorship. Cold temperature and high density cause reduced survivorship, but these stresses do not cause repeatable changes in the phenotypic variance of most wing morphological traits. Wing area, however, does show increased phenotypic variance under both types of environmental stress. This increase is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
4
41
1
Order By: Relevance
“…Several studies have confirmed that inbreeding depression is more pronounced in a stress environment (Bijlsma et al, 2000 and references therein). Other studies however failed to find this (Armbruster et al, 2000;Fowler and Whitlock, 2002).…”
Section: Lifespan In Inbred Drosophilamentioning
confidence: 78%
See 2 more Smart Citations
“…Several studies have confirmed that inbreeding depression is more pronounced in a stress environment (Bijlsma et al, 2000 and references therein). Other studies however failed to find this (Armbruster et al, 2000;Fowler and Whitlock, 2002).…”
Section: Lifespan In Inbred Drosophilamentioning
confidence: 78%
“…Inbreeding is known to lead to general decreases in various fitness measures, and also to very specific linespecific effects in Drosophila (Fowler and Whitlock, 2002) and in Tribolium (Pray and Goodnight, 1995). In a similar fashion, lifespan can be affected by inbreeding in these two different ways.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…I: inbred juveniles; O: outbred juveniles; Pa: parental generation juveniles; < : significantly lower; = : not significantly different; > : significantly higher; na: no significant difference overall, therefore Bonferroni post hoc test was not performed (Table 2). For example, in C. convexa, inbreeding substantially decreased mean female fecundity (>11% reduction, Fowler & Whitlock 2002), an effect not seen in C. fornicata. Inbreeding also largely decreased mean growth rates for juveniles of C. convexa reared at all 3 temperatures and both food levels tested, but had no effect on juvenile growth rates for C. fornicata reared under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…That is, observed environmental differences in the magnitude of the correlation could be simply attributable to the environmental effects on the respective (sex-specific) genetic variances. Predicting the effects of a novel environment on the expression of genetic variance is difficult because there are numerous theoretical (and biologically plausible) possibilities and empirical data are equivocal, with documented instances of both inflation and contraction of variances attributable to environmental effects (e.g., Hoffmann, 1998, 2004;Hoffmann and Merilä, 1999;Fowler and Whitlock, 2002;Charmantier and Garant, 2005). However, a simple expectation is that r w FM may vary as a function of absolute fitness, with the extent of sexually concordant genetic variance being positively related to distance from the optimum (e.g., a positive r w FM when a population is far from a fitness peak, and hence at low fitness, characteristic of the early stages of adaptation).…”
Section: Introductionmentioning
confidence: 99%